Mediation in Peer Interaction - Dawadi, Saraswati (Journal of NELTA, 2015)
This article examines the strategies used by the high-level English as a foreign language learners to mediate understanding in peer interactions. The data was generated from peer interactions of post graduate level students in their regular classroom. It was found that the students were able to understand communicative intent of their peers and provide support to each other; they worked collaboratively and co-constructed knowledge. They used different strategies to mediate understanding. The major strategies included: repetition, elaboration, definition, contextual cues, scaffolding, paralinguistic cues and real life examples. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12079 Journal of NELTA, Vol 19 No. 1-2, December 2014: 47-55